1999
DOI: 10.2307/1468459
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Bryophytes in Stream Ecosystems

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Abstract. Aquatic bryophytes are a common but often overlooked component of a wide variety of stream ecosystems. Although stream environments present a number of challenges for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The role of bryophytes in accumulation of nitrogen in the soil is discussed in numerous publications (Brisbee et al, 2001). It has been established that the dead part of moss cover has rather high hydrolytic acidity, thanks to this factor the moss bedding is characterized by essential absorption ability and can contain not only hydrogen ions in great quantities, but also other elements necessary for plants (Bowden et al, 1999). It has been established in arctic ecosystems that some species of Sphagnum genus as well as Hylocomium splendens (Hedw.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of bryophytes in accumulation of nitrogen in the soil is discussed in numerous publications (Brisbee et al, 2001). It has been established that the dead part of moss cover has rather high hydrolytic acidity, thanks to this factor the moss bedding is characterized by essential absorption ability and can contain not only hydrogen ions in great quantities, but also other elements necessary for plants (Bowden et al, 1999). It has been established in arctic ecosystems that some species of Sphagnum genus as well as Hylocomium splendens (Hedw.)…”
Section: Discussionmentioning
confidence: 99%
“…Bryophytes are the first to colonise dump substrates, gradually forming dense, multispecific cover. The important role of mosses as pioneer plants is well-known (Bowden et al, 1999;Bueno de Mesquita et al, 2017). The gradually dying off of the pioneer bryophyte species prepares the substrate for other mosses and vascular plant populations.…”
Section: Introductionmentioning
confidence: 99%
“…Semi-aquatic bryophytes such as B. frigidum are understood to draw the majority of their nutrients from stream water [1], so it is possible that differences in nutrient availability subsequent to harvest treatments may affect bryophyte productivity. Future controlled experiments should seek to measure the response of semiaquatic bryophytes to increased stream nitrate levels.…”
Section: Timber Harvest Microclimate and Bryophyte Morphologymentioning
confidence: 99%
“…Multiple authors have identified the need for studies that investigate bryophyte response to post-timber har-vest environments [1][2][3][4][5][6]. Bryophytes are widely distributed among terrestrial and aquatic environments [7,8] and serve a number of important roles in forested ecosystems by contributing greatly to net primary productivity, nutrient retention, and by providing habitat and a food base for invertebrates [1,3,9]. Binkley and Graham [10] found that bryophytes made up an average of 5% net primary productivity, 20% of the understory biomass, and 95% of the understory photosynthetic tissue in an old-growth Douglas-fir forest of the pacific northwest, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic bryophytes are important organisms of freshwater ecosystems and, as primary producers, influence biodiversity by changing the environmental conditions and the nutrient dynamics (Bowden, 1999). Some evidence suggests that their cell walls have greater storage capability than the cellular cytoplasm and that PAHs potentially can fill up this compartment of the leaf before moving into the cytoplasm of the cells (Keyte et al, 2009).…”
Section: Introductionmentioning
confidence: 99%